PENGARUH KOMPETENSI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PADA CV ELRAYA KEDIRI - Krisna, Daffa; Jatmiko, Udik; Hendratmoko, Suseno (Cahaya Ilmu Bangsa, 2024)
Abstract. In a company or organization, human resources (HR) are an important component because the success of the company depends on the role of the individuals in it. Internal elements in a company, such as work culture and competencies that are in line with the ability of individuals to carry out tasks and responsibilities, can affect the quality of performance and success in achieving goals. This study aims to determine the